KOMUNIKASI KELUARGA DALAM PERKEMBANGAN ANAK - Sari, Afrina (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
This study aims to describe patterns of family communication in child development. Design research is a descriptive survey using a statistical test of causality by Structural Equation Model (SEM) using LISREL and SPSS version 16 for conform and look at the model equation. The results showed that (1) Effect of verbal language, intonation, tone of the physical development of children is 0.210 and the other is the influence of other variables (errorvar) of 0.790. Effect of verbal language, intonation, tone of emotional development of children is 0.329 and the other is the influence of other variables (errorvar) of 0.671. Effect of verbal language, intonation, tone of the child's cognitive development is 0.138 and the other is the influence of other variables (errorvar) of 0.862. Effect of verbal language, intonation, tone of the psychosocial development of children is 0.0955 and the other is the influence of other variables (errorvar) of 0.905. (2) Effect of nonverbal communication facial expressions, proximity, and hectic kinesics against physical development of children is 0.136 and the other is the influence of other variables (errorvar) of 0.864. Effect of facial nonverbal communication, proximity, hectic and kinesics to the development of the child's emotions is 0.240 and the other is the influence of other variables (errorvar) of 0.760. Effect of nonverbal communication facial expressions, proximity, hectic and kinesics of cognitive development of children is 0.130 and the other is the influence of other variables (errorvar) of 0.870. Effect of nonverbal communication facial expressions, proximity, hectic and kinesics of the psychosocial development of children is 0.0977 and the other is the influence of other variables (errorvar) of 0.902.